HUBUNGAN KUALITAS PELAYANAN DOKTER GIGI MUDA DALAM PERAWATAN GIGI TIRUAN LENGKAP AKRILIK TERHADAP KEPUASAN PASIEN - Afina Ridoti; Debby Saputera; Riky Hamdani; Galuh Dwinta Sari; Aulia Azizah (Universitas Lambung Mangkurat, 2024)
Background: Dentures are dental prostheses that are used to replace lost teeth and tissues. Patients who believe that denture care services are frequently visited throughout treatment are the most likely to seek dental care. Objective: Analyzing the association between young dentists' service quality in the treatment of acrylic complete dentures and patient satisfaction at the Gusti Hasan Aman Oral Dental Hospital. Method: The study used an observational-analytic method with a cross-sectional research design and a simple random sampling technique. A sample of 38 people was obtained using a research instrument, namely a questionnaire. Results: According to the study's findings, the majority of complete denture users at the Gusti Hasan Aman Oral Dental Hospital were between the ages of 55 and 64 (55-64%). According to the gender of the study's findings, the majority of complete denture users at the Gusti Hasan Aman General Hospital (60.52%) were women. According to the study's findings based on education level, the majority of complete denture users at the Gusti Hasan Aman General Hospital were elementary school educated (50%). According to the findings of the study on the service quality of young dentists, the majority of patients (98.4%) believed they received satisfactory service. Patients were satisfied with the treatment (84.2%), according to the results based on patient satisfaction. The findings of the Somer's d test were 0.000. Conclusion: The service quality of RSGM is generally extremely good, and acrylic complete denture patients who are treated are highly delighted.Keywords: Dentures, Patient Satisfaction, Service Quality